COMPUTER LITERACY OF STUDENTS OF HIGH EDUCATION INSTITUTIONS - Krstić, Kristina (ACADEMIC REVIEW, 2022)
An anonymous questionnaire with 12 questions in the form of tables and open-ended questions was applied to a sample of 48 respondents, 38 female and 10 male students divided into four majors, i.e. four study programs of the University of Bijeljina. In this paper, it was considered which skills and competences are necessary for participation in the information society and where and in what way new skills and competences, ie information literacy, should be developed. The results showed that students understand the concept of information literacy in different ways and that based on the obtained data it can be concluded that the importance of all levels of education for the development of information literacy is recognized. The results showed that the practice of developing information literacy at a higher education institution is not sufficiently established, although there is a practice of using technology in teaching processes and for learning purposes.